GURU BHAKTI DALAM TAITTRIYA UPANISAD - Ni Luh Ratna Sari; I Gede Suwantana (Perkumpulan Organisasi Profesi DPP Dosen Hindu Indonesia (DHI) Bekerja sama dengan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar dan Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
Guru is a central position in the spiritual world. Spiritual learning without teacher guidance will have no impact. In the Upanishads, the teacher is the key to the success of a student. Those who learn from a teacher, spiritual development can be known stages. One of the texts that discusses the importance of the teacher's presence in the spiritual tradition is the Taittiriya Upanisad. This work descriptively describes how devotion to the teacher is good and right so that it has a direct impact on spiritual success. The teacher is a god who has the form of an id on the face of the earth. From the teacher spiritual lessons can be transferred and transformed into students. Gurus are those who understand the teachings of the Vedas (srotriya) and who have experienced self-realization/merge with Brahman (brahmanistha). The teacher becomes a guide because he has directly experienced the highest consciousness. Likewise, the teacher is able to teach it in accordance with the development of students' awareness. On that basis the teacher deserves respect, and with the respect given, the spiritual process can run optimally.